Hyperaccumulation and Mobility of Heavy Metals in Vegetable Crops in India - J.I., Nirmal Kumar; Soni, Hiren; Kumar, Rita N.; Bhatt, Ira (Journal of Agriculture and Environment, 2009)
The heavy metals or trace elements play an important role in the metabolic pathways during the growth and development of plants, when available in appreciable concentration. The heavy metal concentration of Cadmium (Cd), Cobalt (Co), Copper (Cu), Iron (Fe), Nickel (Ni), Lead (Pb) and Zinc (Zn) was analyzed using Inductive Coupled Plasma Analyzer (ICPA) (Perkin-Elmer ICP Optima 3300 RL) in 18 vegetable crop plants and their parts along with their soil, collected from various agricultural fields around Anand province, Gujarat, India. The vegetables crop plants were Anthem (Anthum graveolens), Beat (Brassica oleracea), Bitter Gourd (Momordica charantia), Brinjal (Solanum melongena), Cauliflower (Brassica oleracea var. botrytis), Chilli (Capsicum annum), Coriander (Coriandrum sativum), Fenugreek (Trigonella foenum-graceum), Garlic (Alium sativum), Coccinia indica, Lufa (Luffa acutangula), Lady's Finger (Abelmoschus esculentus), Mint (Mentha piperata), Radish (Raphanus sativum), Spinach (Spinacia oleracea), Tomato (Lycopersicum esculentum), Vetches (Cyamopsis soralioides) and White Gourd (Lagernaria vulgaris). The Accumulation Factor (AF) and Mobility Index (MI) were calculated for assessment of mobility of heavy metals from soil to various plant parts: roots, stems and leaves through different levels: Level 1 (Soil-Roots), Level 2 (Roots-Stems) and Level 3 (Stems-Leaves) in studied vegetable crop plants. The results showed concentration dependent variables of heavy metal levels among vegetable crop plants. The lower and higher concentration gradient alongwith their mobility gradient was also determined. A perusal of data reflects that accumulation gradient of each crop plant component vary according to their nature, properties and podsol climate of a particular crop plant. The data on accumulation and mobility of heavy metals such as Cd, Co, Cu, Fe, Ni, Pb and Zn from soil to leaves through roots and stems, suggested that all the metals were highly mobile. Key words: Vegetable crop plants; Heavy metals; Accumulation factor; Mobility index; etc. The Journal of Agriculture and Environment Vol:10, Jun.2009 page: 34-45